Personal tools

99 questions/Solutions/5

From HaskellWiki

< 99 questions | Solutions(Difference between revisions)
Jump to: navigation, search
m (tagged the implementation found in prelude.)
 
Line 23: Line 23:
 
reverse' (x:xs) reversed = reverse' xs (x:reversed)
 
reverse' (x:xs) reversed = reverse' xs (x:reversed)
 
</haskell>
 
</haskell>
  +
  +
  +
[[Category:Programming exercise spoilers]]

Latest revision as of 19:52, 18 January 2014

(*) Reverse a list.

reverse          :: [a] -> [a]
reverse          =  foldl (flip (:)) []

The standard definition, found in the prelude, is concise, but not very readable. Another way to define reverse is:

reverse :: [a] -> [a]
reverse [] = []
reverse (x:xs) = reverse xs ++ [x]

However this definition is more wasteful than the one in Prelude as it repeatedly reconses the result as it is accumulated. The following variation avoids that, and thus computationally closer to the Prelude version.

reverse :: [a] -> [a]
reverse list = reverse' list []
  where
    reverse' [] reversed     = reversed
    reverse' (x:xs) reversed = reverse' xs (x:reversed)